Demand for mobile internet: Evidence from a real-world pricing experiment - Maija Gao; Ari Hyytinen; Otto Toivanen (The Research Institute of the Finnish Economy (ETLA), 2004)
Mobile phones are increasingly used as a gateway to the Internet. The take-up of mobile phone-enabled Internet services was, however, initially slower than expected, at least in Europe. We estimate non-parametrically the price elasticities of demand for first-generation wireless services using (i) consumerlevel panel data from a real world pricing experiment and (ii) the restrictions of a structural model. We decompose the number of wireless connections into the number of needs and the conditional probability of establishing a connection, given a need. According to our estimates needs were plenty, but the conditional usage probability small. Demand for first-generation wireless services was highly elastic and the welfare gains to an (early) adopter moderate. Pricing and taxation of wireless services had a large suppressing effect on demand
Keywords: L11; D12; 330; Wireless internet; demand; new products; welfare; Mobilkommunikation; Internet; Preiselastizität; Nachfrage; Medienverhalten; Test; Finnland